Using YouTube to Improve Students’ Speaking Skill in Teaching Procedure Text - Lintang Kusuma; Zahriyanda Benti Syam (UM Purwokerto Press, 2022)
English has become an international language, so the mastery of English language skills is important. However, the students still face some problems that make them unmotivated and hinder speaking. Considering these situations and conditions, the teacher must address this challenge and determine the most effective strategy for involving students in the teaching and learning process, particularly in speaking. As a result, YouTube is selected as one of the options for teaching speaking in this article in order to determine how using YouTube in teaching procedure text might improve students' speaking skills. On the basis of the literature review and the application of YouTube in the classroom, it is concluded that YouTube can be beneficial to enhance students' speaking skills in teaching procedure text.